Klebsiella capsular type versus site of isolation. Issue 5 (May 1981) - Riser, E; Noone, P
Abstract : More than 1750 clinical isolates of klebsiella were collected over a period of six years from two different hospitals and capsular typed by the fluorescent antibody technique. A correlation was made between type and site of isolation. Many types were found to be associated more frequently with one site, which suggested a predilection of some capsular types for certain sites of infection. The site may also be a factor contributing to the virulence of a particular type. A greater antibiotic resistance was often noted in types isolated from their predominant sites; however, antibiograms were not consistent for a type from a given site. The combination of site specificity, resistance, and another 'virulence factor' may all be involved in the determination of a pathogenic strain.